Photodynamic inactivation of viruses. Prototypes. Understanding and grounding - Torianyk, Inna; Minukhin, Valery; Melentieva, Khristina; Moiseenko, Tetyana; Khristian, Gennady; Melnik, Anatoliy; Bolshakova, Galina (Annals of Mechnikov’s Institute, 2023)
Introduction. Discussions around the problem of photodynamic methods of virus inactivation, considering the effectiveness of using their most verified results in the creation of vaccines (live, inactivated, subunit, recombinant, synthetic; toxoids), orient the scientific community to a detailed analysis and non-pragmatic objectification of key prototypes as means scientific and theoretical grounding of issues by topic. The leading prerogative of such an approach (meta-analytical) is the aggregation of information to a higher degree of statistical power, greater assessment reliability than can be obtained from the results of individual studies. The study of abstract analyzes (retrospective, including) based on the results of photodynamic inactivation of viruses with the aim of applying the obtained phenomena for the creation, testing and production of vaccines showed the presence of a small number of sources on the search topic (both in Ukraine and abroad). Taking a careful approach to the tasks and being aware of the fact that it is impossible at this stage to develop a unified assessment that is close to the general truth that is little known to us today (the production of vaccines by photodynamic inactivation methods), the analysis of the specific problems of scientific sources was carried out on several hundred informative annals. In accordance with the given search parameters, the principles recommended by the compilers of the Cochrane Collaboration were followed, using a combination of evidence / information from qualitative studies, for the evidential context of systematic reviews (by prototypes: viruses, identification, characterization, metabolism and cellular structures; inactivation; photodynamic methods; vaccines. By the way, a successful solution to the problem of photoinactivation of viruses is unequivocally focused on the plane of comprehensive awareness of the biological essence of the latter). Purpose: to conduct an analysis of modern and retrospective analyzes of reference sources regarding the problem of photodynamic inactivation of viruses and the subsequent application of the results for the creation of vaccines. Materials and methods. The material of the study was the reference annals (retrospective, including), archives, copies of laboratory samples based on the results of photodynamic inactivation of viruses with the aim of applying the obtained phenomena for the creation, testing and production of vaccines. The scope of the study was completed with data from many years of development (primary material from experimental studies, copies of excerpts from reports; fragments-sections of current research works on the problem of photoinactivation of viruses on the bacteriophage model), obtained in the laboratory of viral infections of the State Administration "Institute of Microbiology and Immunology named by I.I. Mechnikov of National Academy of Medical Sciences of Ukraine" (2021-2023). In order to objectify the work, an extended analytical review of thematic sources of scientific-theoretical, methodological, patent information was conducted (according to the key prototypes specified above). The search was conducted using the databases of bibliographic resources of search engines "Google", "Yandex", "Rambler" and others. Results& Discussion. The authors note that the identification of viruses contributes to the application of refined photoinactivation algorithms, obtaining decisive results in terms of qualitative and quantitative parameters. It is an obvious factor in the objectification of the latter. Virus identification is the basis of thorough data verification. One of the pragmatic goals of the universal taxonomic system (UTS) is the identification of viruses. Despite the fact that it is built on conventionally chosen hierarchical levels (family, genus, species, strain, variant), the adjective "unequivocal" is firmly implanted in the term "identification". The brevity of the UTS does not prevent researchers from indicating the belonging of each of the viruses used in scientific development to the appropriate taxon. Characteristics of viruses are obtained due to visualization and the results of ultramicroscopic studies using negative contrast, serological methods, determination of resistance to various factors (changes in pH, temperature, effects of certain types of solvents (lipids), etc.). An important integral parameter remains the morphology of the virion. The specified identification and characterization have proven effectiveness over the years, which contributes to the optimal selection and support of experiments on photoinactivation of viruses and their extrapolations into practice. The article emphasizes that the accumulated data on metabolism and cellular structures testify in favor of the implementation of several cardinal principles of detection of inhibitory properties of physicochemical (photodynamic, including) effects on viruses. Studies of the common physical factors affecting the viability of viruses today are focused, first of all, on certain types of exposure. Irradiation is not only a factor of inhibition and destruction of viruses, but also a rather effective measure in the study of their structural and functional dominance. It is shown that in the study of viruses, their adaptation potential to environmental conditions, radiobiological methods have acquired one of the most appropriate applications. Research on the use of X-ray irradiation to promote the development of torpidity of viruses is known to the scientific chronicle; short-wave high-energy radiations of radioactive substances and those obtained under the conditions of modern accelerators. Solving the complex and multifaceted problem of virus inactivation (photodynamic as an example) is inextricably linked to the use of the host’s immune resources. The authors analyzed the results of the use of model bacteriophages, showed the prospects of the specified methods. The article also emphasizes the photodynamic inactivation of viruses as one of the ways to obtain vaccine preparations. Соnclusions. A successful solution to the problem of photoinactivation of viruses is clearly focused in the plane of comprehensive awareness of the biological essence of the latter, leading aspects of their identification, characteristics, metabolism and participation of host cell structures. Photodynamic inactivation is a comprehensive multicomponent process, for the effective implementation of which complex approaches and an assortment of "stimulators" are extremely necessary. Photoinactivation is impossible without basic efficiency markers and consideration of potential compensatory reactions. Key words: viruses, identification, characterization, metabolism and cellular structures; photodynamic inactivation, methods, photosensitizers, photoreactivation; lysis; immune resources of the host.